Prehistoric relief transformation at the archaeological site Rychnowo V in upper Drwęca River basin: https://doi.org/10.26485/AGL/2018/107/1 - Kalicki, Tomasz; Chrabąszcz, Mariusz; Maciszewski, Igor; Przepióra, Paweł (Acta Geographica Lodziensia, 2018)
The results of geoarchaeological and archaeological research at the Rychnowo V site are presented. The archaeological site is located on the moraine plateau between two subglacial tunnel valleys currently drained by the upper Drwęca and Grabiczek Rivers. Relief of the moraine plateau is varied by hollows on post-glacial depressions of varying size and degree of filling. These lakes were formed in the Late Glacial and were filled in the Holocene by organic and clastic deposits. At the archaeological site, several settlement phases have been identified related to the Lusatian (main phase) and Wielbark cultures, Early and Late Medieval and Modern periods. Not found in the site permanent or long-term settlement. The site should be considered as group of rather short-lived camps. The most numerous traces of Lusatian culture are not a single phase, but rather multiple returns to the same area at short intervals (the homogeneous ceramics). The activity of the people of Lusatian culture (connected not with cultivation but grazing) at the beginning of the Subatlantic led to slope erosion and soil fossilization in endorheic depression.